Assessment of the Value of Rescreening for Syphilis in the Third Trimester of Pregnancy - Rodney K. Edwards; Margaret Bennett; Carrie Langstraat; Daina Greene (Hindawi Limited, 2006)
Objectives. Our aim is evaluating the need for repeating tests for syphilis on pregnant women in the third trimester. Study design. A single-center retrospective cohort study was performed on all women delivering 7/03-6/04. Results. During the study interval, 2244 women delivered at our hospital. Of those women having available records and attending at least one prenatal visit, 1940 (98.9%) were screened for syphilis at the first prenatal visit. Of the 1627 women beginning prenatal care prior to 27 weeks and delivering after 32 weeks, 1377 (84.6%) were rescreened in the third trimester. No cases of syphilis were identified with either the initial (upper limit of 95% CI 0.24%) or repeat (upper limit of 95% CI 0.34%) screening. Conclusions. In our obstetric population, syphilis is so uncommon that mandated prenatal screening on more than one occasion seems unjustified and laws requiring repeated screening should be reevaluated.